Analysis of the Readiness of Home-Based Industries to Adopt E-Money in Aceh Province, Based on the Unified Theory of Technology Acceptance - M. Saleh; M. Shabri Abd. Majid; Suriani; Hamdani; Muhammad Rizal; Hakim Muttaqim (JURNAL ILMIAH GEMA PERENCANA, 2026)
The Fourth Industrial Revolution has driven various advancements in technology, one of which is marked by the emergence of the digital revolution that has impacted payment systems, including the use of electronic money (E-money) in financial transactions. The home industry plays a strategic role in supporting national economic development, where innovations in technology-based transaction systems have a significant impact on the sustainability and efficiency of their business activities. One of the rapidly developing innovations today is the use of e-money. The research method employed is a quantitative approach based on the UTAUT model. Data were collected through interviews and the distribution of questionnaires designed using a Likert scale, with questionnaire items based on the variables in the UTAUT model. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via the SmartPLS software. The results indicate that the intention to use e-money drives actual usage behavior. Ease of use and social influence enhance this intention, while perceived benefits have not yet emerged as a determining factor. Furthermore, facility support plays a crucial role in driving e-money usage within the home industry in Aceh.